Evaluation of a multidisciplinary epilepsy transition clinic for adolescents. (May 2016) - Geerlings, R.P.J.; Aldenkamp, A.P.; Gottmer-Welschen, L.M.C.; de With, P.H.N.; Zinger, S.; van Staa, A.L.; de Louw, A.J.A.
Abstract: Introduction: The main goal of the transition clinic is to explore and optimize medical issues during transition from adolescence to adulthood, and to ease the transition into adult care. However, only limited data on the process and outcomes of transitional care in clinical practice are available. Objective: To describe the process and outcomes of an Epilepsy Transition Clinic in a tertiary referral center in The Netherlands. Methods: Data were collected from patients with epilepsy (aged 15–25 years), who visited the transition clinic between March 2012 and September 2014. Results: The Epilepsy Transition Clinic is staffed with a multidisciplinary team including a neurologist/epileptologist, clinical neuropsychologist, a social worker and an educationalist/occupational counselor, all with knowledge of paediatric and adult medical and developmental issues. In total, 117 patients with epilepsy were included in the analysis. After consultation, 89 patients received a diagnostic work-up (76.1%), change in AED prescription ( n  = 64, 54.7%), or consultation/tailored advice ( n  = 73, 62.4%). In fourteen patients (12.0%) the epilepsy diagnosis was changed. Nineteen patients (16.2%) had complete epilepsy remission for over one year. Forty-three patients (36.8%) were referred to adult care. Conclusion: This study describes a multidisciplinary epilepsy transition clinic staffed by a neurologist/epileptologist, neuropsychologist, a social worker and an educationalist/occupational counselor. Diagnostic work-up and evaluation of psychosocial and educational/vocational status during adolescence are strongly recommended. Highlights: We describe the process and outcomes of a multidisciplinary epilepsy transition. Our transition clinic revises medical and psychosocial issues before transition. The collaboration with a psychologist, educationalist and social worker is important. After a diagnostic work-up, diagnosis and treatment are optimized. Validated questionnaires to examine development and transition readiness exist.